2017
DOI: 10.7326/m16-1881
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pay-for-Performance Programs on Health, Health Care Use, and Processes of Care

Abstract: U.S. Department of Veterans Affairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
248
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(258 citation statements)
references
References 79 publications
4
248
1
5
Order By: Relevance
“…Other than the possibility that physician incen- tives in general may not be effective, there are several reasons that may explain the failure of this particular incentive to improve follow-up rates. 26 First, incentive payments were received along with other claim payments, possibly obscuring their effect on income. Second, payments were typically received weeks to a month later, doing little to reinforce the incentivized behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the possibility that physician incen- tives in general may not be effective, there are several reasons that may explain the failure of this particular incentive to improve follow-up rates. 26 First, incentive payments were received along with other claim payments, possibly obscuring their effect on income. Second, payments were typically received weeks to a month later, doing little to reinforce the incentivized behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] It is uncertain whether financial incentives to physicians improve quality of care. [24][25][26] However, such incentives may be one way to increase rates of early follow-up. In 2013, the Centers for Medicare and Medicaid Services introduced transitional care management codes to the US, which provide additional reimbursement to physicians offering early patient follow-up.…”
mentioning
confidence: 99%
“…A systematic review of pay-for-performance studies published in the USA, the UK and Taiwan suggested that while these programmes may result in improved processes of care in the ambulatory setting, a finding driven largely from studies of the UK’s QOF programme, associations with improved health outcomes have yet to be demonstrated 2. Within the UK, for example, the QOF was not found to be associated with significant changes in mortality, ischaemic heart disease or cancer 3…”
Section: Quality Of Care In the United Kingdom After Removal Of Finanmentioning
confidence: 99%
“…Linking compensation with achieving arbitrary benchmarks conflicts with practicing shared decision making wherein the quality measure is the adequacy of the shared-decision-making encounter, not the prevalence of the eventual outcome chosen by the patient. 2 These perverse incentives made me a worse doctor as indicated by failing to meet the benchmarks.…”
Section: Point/counterpointmentioning
confidence: 99%
“…The fact that we are increasingly being paid according to these systems, but are still debating their effectiveness, is a call to action. 1,2 Figure 1 outlines a model that I have used over the past 30 years to improve quality of patient care. Let us walk through the model step by step.…”
mentioning
confidence: 99%